KARAKTERISTIK KIMIA DAN ORGANOLEPTIK ENERGY SNACK BAR DENGAN SUBSTITUSI EMPING SINGKONG (Cassava Flakes) - Nasiroh, Fahra Fahrihatun; qudus, Ati Atul Quddus atul; tubagus, Robi (Jurnal Pangan dan Gizi, 2024)
Abstract Cassava flakes have a high carbohydrate content so they can be used as an energy source food product. Cassava flakes can be used as a source of carbohydrate substitution for corn flakes as raw material for making energy snack bar products. This study aims to determine the effect of the chemical and organoleptic characteristics of the energy snack bar with substitution cassava flakes and also to find out the organoleptic characteristics of the best energy snack bar with the substitution of cassava flakes which is preferred by the panelists.. The experimental design used was a Completely Randomized Design (CRD) with four treatments, namely P0 (without substitution cassava flakes), P1 (50% substitution cassava flakes), P2 (75% substitution cassava flakes), P3 (100% substitution cassava flakes). Based on tne results of the research that has been done, it can be concluded that the substitution of cassava flakes has a significant effect on the value of water content, ash content, protein content, fat content, carbohydrate content and total calories. It also has a significant effect on the attributes aroma, color, texture and overall but no significant effect on the attributes taste. The best treatment for cassava flakes substitution in energy snack bar products based on the organoleptic characteristics is treatment P1 (50% substitution cassava flakes), with taste attribute characteristics of taste 5,48 (rather like), aroma attribute 5,08 (rather like), color attribute 5,24 (rather like), textute attribute 5,24 (rather like) and overall product total 5,36 (rather like).